Nasal columella reconstruction – A comprehensive review of the current techniques. Issue 5 (May 2020) - Nowicki, Jake; Abbas, Jonathan R.; Sudbury, Danny; Anari, Shahram
Summary: The nasal columella is often described as being one of the most difficult nasal subunits to reconstruct. There are a wide range of indications for columella reconstruction, with defects resulting from ischaemic injuries, trauma, tumour resection, vascular malformations and congenital agenesis/dysgenesis of nasal anatomy. There is a variety of columella reconstruction techniques reported in the literature, giving reconstructive surgeons options when approaching different columella defects. Each technique has surgical pearls and pitfalls as well as advantages and disadvantages. This review aims to give reconstructive surgeons a comprehensive review of currently used columella reconstruction techniques.